Alice in the country of clover. The March Hare's revolution. (Seven Seas Entertainment, 2015)
"Alice has been whisked to the Country of Clover, but at least her home-- Hatter Mansion-- came along for the move. Her intimate friendship with Elliot gives her strength to face the new challenges, but he's a man of contradictions, and she's uneasy about his hard mobster interior lurking behind the grinning goofball exterior. When she starts to fall for him, however, memories of her past world resurface that being to sway her. Clover is a dangerous place for hesitation. Beware the talking doors!"--Page 4 of cover.